Preparation method of UV viscosity-reducing adhesive tape
By the preparation method of UV -reducing tape, the light activity monomer is directly connected to the base rubber skeleton branches and added auxiliary agent to solve the high residual pollution of the existing UV -reducing tape on the silicon wafer. The problems such as low internal agglomeration have achieved the effect of high -stripping force and low viscosity, and improved processing performance and use performance.
Patent Information
- Application Number
- CN202411445540.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-24
AI Technical Summary
The problems of existing UV adhesive tape on silicon wafers, such as high residual contamination wafers, low cohesion, stability, poor compatibility and edge spills, are difficult to meet the needs of higher performance.
Adopt a method of preparation of UV -reducing tape to heat up and co -convergence by adding heat cause agents to acrylic monitors to obtain base gel; then add light active monomer and active tin reagent to the base glue for heating. Light activity pressure -sensitive glue; then add the light cause and auxiliary agent for mixing to obtain UV reducing glue; finally, the UV reduction glue was coated on the substrate layer for baking Sticky tape.
The UV -reducing tape has high -stripping force before UV light, and the effect of decreased viscosity after UV light shooting, improving the processing performance and use of UV -reducing glue, without pollution and no residue.
Smart Images

Figure CN119351008A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesive materials, and more particularly to a method for preparing a UV anti-viscosity tape. Background Art
[0002] Wafer materials need to be fixed and protected with UV anti-sticking tape during the cutting and grinding process. The function of this type of tape is to provide sufficient initial adhesion before UV irradiation to protect the wafer during cutting or etching processes. After UV irradiation, it should be easy to remove with as little residual glue and pollution as possible.
[0003] So far, the research on this type of tape is mainly based on the "hybrid type", (1) acrylic copolymer, multifunctional monomer, photoinitiator mixed compound; (2) acrylic / polyurethane polymer, multifunctional oligomer / acrylate monomer, photoinitiator mixed compound. Representative examples are as follows: 1) In 2012, Lee et al. used acrylic copolymer, hexafunctional acrylic monomer as diluent, methyl aziridine derivative as crosslinker, and mixed with photoinitiator to prepare acrylic UV viscosity-reducing adhesive. After UV curing, the peeling ability was 7.8N / 25mm (Lee SW, Park JW, Lee YH, et al. Adhesion performance and UV-curing behaviors of interpenetrated structured pressure sensitive adhesives with 3-MPTS for Si-wafer dicing process [J]. Journal of Adhesion Science and Technology, 2012, 26: 1629-1643.). 2) In 2006, Do and his colleagues used acrylic copolymers and unsaturated photoinitiators to react to prepare acrylic UV viscosity-reducing adhesives. After UV light curing, the peeling ability was 4.9N / 25mm (Do HS, Park YJ, Kim HJ. Preparation and adhesion performance of UV-crosslinkable acrylic pressure sensitive adhesives [J]. Journal of Adhesion Science and Technology, 2006, 20: 1529-1545.). 3) In 2022, Ren Fengmei's research group first reacted terminal hydroxyl polybutadiene (HTPB) with isophorone diisocyanate (IPDI), and then used 1,4-butanediol or 1,4-butenediol as a chain extender to obtain the polyurethane adhesive HTPB-IPDI-I / II. Then, multifunctional acrylate cross-linking monomer and photoinitiator were added to prepare polyurethane-type UV viscosity-reducing adhesive. Before and after UV irradiation, the peeling ability dropped from 19N / 25mm to 0.2N / 25mm (Jiao Shanshan, Ren Fengmei, Wu Xing, et al. Synthesis and properties of polyurethane-type UV viscosity-reducing adhesive based on terminal hydroxyl polybutadiene [J]. Polymer Materials Science and Engineering, 2022, 38(7):1-6.).
[0004] Summarizing the existing "hybrid" methods, it is not difficult to see that since most formulations require the addition of low molecular weight substances such as multifunctional monomers, the following problems exist:
[0005] (1) High residual contamination wafers on silicon wafers;
[0006] (2) Low cohesion, stability, poor compatibility, and edge overflow.
[0007] In summary, how to develop a higher performance "non-hybrid" UV adhesive tape is a problem that technicians in this field need to solve urgently. Summary of the invention
[0008] In view of this, an object of the present invention is to provide a method for preparing a UV anti-viscosity tape to solve the deficiencies in the prior art.
[0009] In order to achieve the above object, the present invention adopts the following technical solution:
[0010] A method for preparing a UV anti-viscosity tape comprises the following steps:
[0011] (1) adding a thermal initiator to an acrylic acid monomer for heating and copolymerization to obtain a base rubber;
[0012] (2) adding a photoactive monomer and an active tin reagent to the base adhesive for heating and grafting to obtain a photoactive pressure-sensitive adhesive;
[0013] (3) adding a photoinitiator and an auxiliary agent to the photoactive pressure-sensitive adhesive and mixing them to obtain a UV viscosity-reducing adhesive;
[0014] (4) coating the UV viscosity-reducing adhesive on the substrate layer and baking the coating to form a UV viscosity-reducing adhesive layer on the surface of the substrate layer;
[0015] (5) Covering the UV anti-viscosity adhesive layer with a release film and curing the film to form a release film layer on the surface of the UV anti-viscosity adhesive layer, thereby obtaining a UV anti-viscosity adhesive tape.
[0016] Furthermore, in the above step (1), the acrylic monomer includes 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate and butyl acrylate in a mass ratio of 9:3:10; the thermal initiator is an azo initiator or a peroxide initiator, such as azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN), dodecyl peroxide, dibenzoyl peroxide, etc., preferably azobisisobutyronitrile, and the amount is 0.1% of the mass of the acrylic monomer; the temperature of the heating copolymerization is 80°C.
[0017] Furthermore, in the above step (2), the photoactive monomer is 2-isocyanatoethyl acrylate or isocyanatoethyl methacrylate, and the amount used is 0.74%-7.5% of the mass of the base rubber; the active tin reagent is dibutyltin dilaurate (DBTDL), and the amount used is 0.074%-0.75% of the mass of the base rubber; and the temperature for heating grafting is 50°C.
[0018] Furthermore, in the above step (3), the photoinitiator is 1-hydroxycyclohexyl phenyl ketone (Irgacure 184), benzophenone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), etc., preferably 1-hydroxycyclohexyl phenyl ketone, and the amount used is 0.4% of the mass of the photoactive pressure-sensitive adhesive.
[0019] Furthermore, in the above step (3), the auxiliary agent is at least one of a surfactant, an antistatic agent and a tackifying resin, and the amount used is 0.2% of the mass of the photoactive pressure-sensitive adhesive.
[0020] Furthermore, the surfactant is γ-methacryloxypropyltrimethoxysilane or diisopropyl di(acetylacetonate)titanate.
[0021] The above further beneficial effect is that the surfactant selected in the present invention can reduce the surface tension of the UV viscosity-reducing adhesive, making it easier to wet the bonded surface, thereby improving the bonding effect. At the same time, the surfactant can also improve the surface properties of the UV viscosity-reducing adhesive after curing, such as improving wear resistance, weather resistance and chemical corrosion resistance.
[0022] Furthermore, the antistatic agent is polyoxyethylene glycerol ether.
[0023] A further beneficial effect of adopting the above is that the antistatic agent selected in the present invention can give the material surface a certain lubricity by forming a conductive layer, reduce the friction coefficient, and thus inhibit and reduce the generation of static charge, which helps the UV viscosity-reducing adhesive to better fit the adherend during application and improve the bonding effect. At the same time, the antistatic agent can significantly reduce the surface resistivity, allowing the generated static charge to leak quickly, thereby effectively curbing the damage caused by static electricity.
[0024] Furthermore, the above-mentioned tackifying resin is C5 petroleum resin or C9 petroleum resin.
[0025] The further beneficial effect of adopting the above is that the tackifying resin selected in the present invention can form a uniform and continuous film on the contact surface through its unique molecular lock structure and rheological properties, thereby increasing the adhesion of the UV viscosity-reducing adhesive. At the same time, the tackifying resin has good rheological properties and can flow quickly and fill surface defects during construction or use, which helps the UV viscosity-reducing adhesive to better penetrate into small pores and improve the coating effect and adhesion performance.
[0026] Furthermore, in the above step (4), the material of the substrate layer is a PET film with a thickness of 50 μm; the coating method adopts a wire rod to control the wet film thickness to 25 μm; the baking equipment is an oven, and the procedure is: first bake at 80°C for 25 minutes, and then bake at 35°C for 12 hours.
[0027] Furthermore, in the above step (5), the material of the release film is PET release film with a thickness of 50 μm; the aging temperature is 25-60° C. and the aging time is 2-7 days.
[0028] It can be seen from the above technical solution that compared with the prior art, the beneficial effects of the present invention are as follows:
[0029] 1. The present invention creatively grafts photoactive monomers directly onto the side chains of the base glue skeleton, and UV viscosity-reducing adhesive can be prepared without the need for subsequent addition of multifunctional monomers or oligomers. At the same time, additives are creatively added to achieve effective regulation of the adhesion and viscosity of the UV viscosity-reducing adhesive, further achieving the effect of high peeling force before UV light irradiation and reduced viscosity after UV light irradiation, thereby improving the processing performance and use performance of the UV viscosity-reducing adhesive.
[0030] 2. The test results show that the UV anti-viscosity tape made from the UV anti-viscosity adhesive of the present invention has high initial adhesion (maximum 19.09N / 25mm), can well protect and fix the protected material, has low peeling force after UV light irradiation (minimum 0.18N / 25mm), is easy to peel off from the protected material, and has the characteristics of no pollution, no residue, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a schematic diagram of the structure of the UV adhesive tape of the present invention;
[0032] Among them, 1-substrate layer, 2-UV anti-adhesive layer, 3-release film layer. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] The preparation method of UV anti-viscosity tape specifically comprises the following steps:
[0036] (1) In a nitrogen atmosphere, 2-ethylhexyl acrylate (45 g, 244.35 mmol), 2-hydroxyethyl acrylate (15 g, 129.2 mmol), butyl acrylate (40 g, 312.1 mmol) and ethyl acetate (150 g, solvent) were first added to a 500 mL four-necked round-bottom flask equipped with a reflux condenser, a mechanical stirrer and a thermometer, and heated to 80° C., and then azobisisobutyronitrile (0.1 g, 0.1 wt% of acrylic acid monomer) diluted in ethyl acetate was slowly added dropwise to the round-bottom flask, stirred for 6 h, and cooled to room temperature to terminate the reaction, thereby obtaining a base gum solution;
[0037] (2) First, a base glue solution (50 g, 40 wt% solution) was placed in a 250 mL round-bottom flask equipped with a mechanical stirrer. Under a nitrogen atmosphere, the base glue solution was stirred at 50° C. for 15 min. Then, 1.46 g (40% mol of hydroxyl group) of 2-isocyanatoethyl acrylate and 0.146 g of dibutyltin dilaurate were dissolved in ethyl acetate and slowly added dropwise to the round-bottom flask. After stirring for 1.5 h, the reaction mixture was cooled to room temperature to terminate the reaction. The final solid content was adjusted to 40% to obtain a photoactive pressure-sensitive adhesive solution.
[0038] (3) adding 0.1 g of 1-hydroxycyclohexyl phenyl ketone and 0.05 g of γ-methacryloxypropyltrimethoxysilane to 25 g of the photoactive pressure-sensitive adhesive solution and mixing them to obtain a UV viscosity-reducing adhesive;
[0039] (4) coating the UV viscosity-reducing adhesive on a 50 μm thick PET film using a 25 μm wire rod coater, pre-baking in an oven at 80° C. for 25 min, and then curing at 35° C. for 12 h to form a UV viscosity-reducing adhesive layer 2 on the surface of the substrate layer 1;
[0040] (5) A PET release film with a thickness of 50 μm is coated on the UV adhesive layer 2, and then aged at 25° C. for 7 days to form a release film layer 3 on the surface of the UV adhesive layer 2, so as to obtain Figure 1 UV-reducing adhesive tape shown.
[0041] Example 2
[0042] The preparation method of UV anti-viscosity tape specifically comprises the following steps:
[0043] (1) In a nitrogen atmosphere, 2-ethylhexyl acrylate (45 g, 244.35 mmol), 2-hydroxyethyl acrylate (15 g, 129.2 mmol), butyl acrylate (40 g, 312.1 mmol) and ethyl acetate (150 g, solvent) were first added to a 500 mL four-necked round-bottom flask equipped with a reflux condenser, a mechanical stirrer and a thermometer, and heated to 80° C., and then azobisisobutyronitrile (0.1 g, 0.1 wt% of acrylic acid monomer) diluted in ethyl acetate was slowly added dropwise to the round-bottom flask, stirred for 6 h, and cooled to room temperature to terminate the reaction, thereby obtaining a base gum solution;
[0044] (2) First, the base glue solution (50 g, 40 wt% solution) was placed in a 250 mL round-bottom flask equipped with a mechanical stirrer. Under a nitrogen atmosphere, the base glue solution was stirred at 50° C. for 15 min. Then, 1.6 g (40% mol of hydroxyl group) of isocyanoethyl methacrylate and 0.16 g of dibutyltin dilaurate were dissolved in ethyl acetate and slowly added dropwise to the round-bottom flask. After stirring for 1.5 h, the reaction mixture was cooled to room temperature to terminate the reaction. The final solid content was adjusted to 40% to obtain a photoactive pressure-sensitive adhesive solution.
[0045] (3) adding 0.1 g of benzophenone and 0.05 g of polyoxyethylene glycerol ether to 25 g of the photoactive pressure-sensitive adhesive solution and mixing them to obtain a UV viscosity-reducing adhesive;
[0046] (4) coating the UV viscosity-reducing adhesive on a 50 μm thick PET film using a 25 μm wire rod coater, pre-baking in an oven at 80° C. for 25 min, and then curing at 35° C. for 12 h to form a UV viscosity-reducing adhesive layer 2 on the surface of the substrate layer 1;
[0047] (5) A PET release film with a thickness of 50 μm is coated on the UV debonding adhesive layer 2, and then aged at 60° C. for 2 days to form a release film layer 3 on the surface of the UV debonding adhesive layer 2, so as to obtain Figure 1 UV-reducing adhesive tape shown.
[0048] Example 3
[0049] The preparation method of UV anti-viscosity tape specifically comprises the following steps:
[0050] (1) In a nitrogen atmosphere, 2-ethylhexyl acrylate (45 g, 244.35 mmol), 2-hydroxyethyl acrylate (15 g, 129.2 mmol), butyl acrylate (40 g, 312.1 mmol) and ethyl acetate (150 g, solvent) were first added to a 500 mL four-necked round-bottom flask equipped with a reflux condenser, a mechanical stirrer and a thermometer, and heated to 80° C., and then azobisisobutyronitrile (0.1 g, 0.1 wt% of acrylic acid monomer) diluted in ethyl acetate was slowly added dropwise to the round-bottom flask, stirred for 6 h, and cooled to room temperature to terminate the reaction, thereby obtaining a base gum solution;
[0051] (2) First, a base glue solution (50 g, 40 wt% solution) was placed in a 250 mL round-bottom flask equipped with a mechanical stirrer. Under a nitrogen atmosphere, the base glue solution was stirred at 50° C. for 15 min. Then, 1.46 g (40% mol of hydroxyl group) of 2-isocyanatoethyl acrylate and 0.146 g of dibutyltin dilaurate were dissolved in ethyl acetate and slowly added dropwise to the round-bottom flask. After stirring for 1.5 h, the reaction mixture was cooled to room temperature to terminate the reaction. The final solid content was adjusted to 40% to obtain a photoactive pressure-sensitive adhesive solution.
[0052] (3) adding 0.1 g of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and 0.05 g of C5 petroleum resin to 25 g of the photoactive pressure-sensitive adhesive solution and mixing them to obtain a UV viscosity-reducing adhesive;
[0053] (4) coating the UV viscosity-reducing adhesive on a 50 μm thick PET film using a 25 μm wire rod coater, pre-baking in an oven at 80° C. for 25 min, and then curing at 35° C. for 12 h to form a UV viscosity-reducing adhesive layer 2 on the surface of the substrate layer 1;
[0054] (5) A PET release film with a thickness of 50 μm is coated on the UV adhesive layer 2, and then aged at 25° C. for 7 days to form a release film layer 3 on the surface of the UV adhesive layer 2, so as to obtain Figure 1 UV-reducing adhesive tape shown.
[0055] Comparative Example 1
[0056] The only difference from Example 1 is that γ-methacryloxypropyltrimethoxysilane is not contained.
[0057] Comparative Example 2
[0058] The only difference from Example 2 is that polyoxyethylene glycerol ether is not contained.
[0059] Comparative Example 3
[0060] The only difference from Example 3 is that no C5 petroleum resin is contained.
[0061] Comparative Example 4
[0062] A commercially available UV adhesive tape.
[0063] Performance Testing
[0064] The UV adhesive tapes prepared in Examples 1-3 and Comparative Examples 1-4 were respectively subjected to pre-UV peel strength test, post-UV peel strength test and residual adhesive test.
[0065] Peel strength test before UV:
[0066] The UV anti-adhesive tape was cut into samples of 250×25 mm in size, the release film was torn off, and the sample was bonded to the cleaned test 304 stainless steel plate. A 2kg pressure roller was rolled back and forth on the sample three times at a speed of 300 mm / min under its own weight (no bubbles were allowed at the bonding point between the sample and the test plate). After the sample was prepared, it was left in the test environment for 30 minutes before the test. A tape peel strength tester (Dongguan Huaguo, model: HG 8603) was used to perform a peeling test at an angle of 180° and a tensile speed of 300 mm / min to obtain the pre-UV peeling strength.
[0067] Post-UV peel strength test and residual adhesive test:
[0068] Cut the UV adhesive tape into 300×25mm size samples, tear off the release film, and bond the sample to the cleaned test 304 stainless steel plate. Use a 2kg roller to roll back and forth on the sample three times at a speed of 300mm / min under its own weight (no bubbles are allowed at the bonding point between the sample and the test plate). 2 After being treated for 5 minutes under a light intensity of , a tape peel strength tester (Dongguan Huaguo, model: HG 8603) was used to perform a peeling test at an angle of 180° and a tensile speed of 300 mm / min to obtain the post-UV peeling strength. After peeling, the surface of the 304 stainless steel plate was observed to see if there was any glue residue to obtain the residual glue test result.
[0069] The results are shown in Table 1.
[0070] Table 1 Test results of peel strength and residual adhesive of UV adhesive tape of Examples 1-3 and Comparative Examples 1-4
[0071]
[0072] It can be seen from Table 1 that, compared with Comparative Example 4, the initial adhesion of the UV viscosity-reducing tapes of Examples 1-3 and Comparative Example 1-3 is significantly improved, and the peeling force after UV light irradiation is significantly reduced; compared with Comparative Examples 1-3, the initial adhesion of the UV viscosity-reducing tapes of Examples 1-3 is further significantly improved, and the peeling force after UV light irradiation is further significantly reduced. The reason is that the present invention creatively grafts photoactive monomers directly onto the branched chains of the base glue skeleton, and the UV viscosity-reducing adhesive can be prepared without the subsequent addition of multifunctional monomers or oligomers. At the same time, the additives are creatively added to achieve effective adjustment between adhesion and viscosity of the UV viscosity-reducing adhesive, further achieving the effect of high peeling force before UV light irradiation and reduced viscosity after UV light irradiation, thereby improving the processing performance and use performance of the UV viscosity-reducing adhesive.
[0073] The above tests show that the UV anti-viscosity tape made from the UV anti-viscosity adhesive of the present invention has high initial tack (maximum 19.09 N / 25 mm), can well protect and fix the protected material, has low peeling force after UV light irradiation (minimum 0.18 N / 25 mm), is easy to peel off from the protected material, and has the characteristics of no pollution, no residue, etc.
[0074] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a UV anti-viscosity tape, characterized in that: The specific steps include: (1) adding a thermal initiator to an acrylic acid monomer for heating and copolymerization to obtain a base rubber; (2) adding a photoactive monomer and an active tin reagent to the base adhesive for heating and grafting to obtain a photoactive pressure-sensitive adhesive; (3) adding a photoinitiator and an auxiliary agent to the photoactive pressure-sensitive adhesive and mixing them to obtain a UV viscosity-reducing adhesive; (4) coating the UV viscosity-reducing adhesive on the substrate layer and baking the coating to form a UV viscosity-reducing adhesive layer on the surface of the substrate layer; (5) Covering the UV anti-viscosity adhesive layer with a release film and curing the film to form a release film layer on the surface of the UV anti-viscosity adhesive layer, thereby obtaining the UV anti-viscosity adhesive tape.
2. The method for preparing a UV adhesive tape according to claim 1, characterized in that: In step (1), the acrylic acid monomer includes 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate and butyl acrylate in a mass ratio of 9:3:10; The thermal initiator is an azo initiator or a peroxide initiator, and the amount used is 0.1% of the mass of the acrylic acid monomer; The temperature of the heating copolymerization is 80°C.
3. The method for preparing a UV adhesive tape according to claim 1, characterized in that: In step (2), the photoactive monomer is any one or both of 2-isocyanatoethyl acrylate and isocyanatoethyl methacrylate; the amount used is 0.74%-7.5% of the mass of the base rubber; The active tin reagent is dibutyltin dilaurate, and the dosage is 0.074%-0.75% of the base rubber mass; the temperature of the heating grafting is 50°C.
4. The method for preparing a UV adhesive tape according to claim 1, characterized in that: In step (3), the photoinitiator is any one or more of 1-hydroxycyclohexyl phenyl ketone, benzophenone, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide. The dosage is 0.4% of the mass of the photoactive pressure-sensitive adhesive.
5. The method for preparing a UV adhesive tape according to claim 1, characterized in that: In step (3), the auxiliary agent is at least one of a surfactant, an antistatic agent and a tackifying resin, and the amount used is 0.2% of the mass of the photoactive pressure-sensitive adhesive.
6. The method for preparing a UV adhesive tape according to claim 5, characterized in that: The surfactant is any one or two of γ-methacryloxypropyltrimethoxysilane and diisopropyl di(acetylacetonate)titanate.
7. The method for preparing a UV adhesive tape according to claim 5, characterized in that: The antistatic agent is polyoxyethylene glycerol ether.
8. The method for preparing a UV adhesive tape according to claim 5, characterized in that: The tackifying resin is any one or both of C5 petroleum resin and C9 petroleum resin.
9. The method for preparing a UV adhesive tape according to claim 1, characterized in that: In step (4), the material of the substrate layer is a PET film with a thickness of 50 μm; The coating method uses a wire rod to control the wet film thickness to 25 μm; The baking equipment is an oven, and the procedure is: first baking at 80° C. for 25 minutes, and then baking at 35° C. for 12 hours.
10. The method for preparing a UV adhesive tape according to claim 1, characterized in that: In step (5), the release film is made of PET release film with a thickness of 50 μm; The aging temperature is 25-60° C. and the aging time is 2-7 days.
Citation Information
Cited By
UV (ultraviolet) viscosity-reducing adhesive as well as preparation method and application thereof
CN121555128A